IMPLEMENTASI KOMBINASI MEDIA KOMUNIKASI ONLINE DALAM PENDIDIKAN GIZI PRAKONSEPSI GENERASI MILENIAL - Yusnia Nur Aziizah; Choirul Anna Nur Afifah (Jurnal Sehat Mandiri, 2021)
Preconception nutrition education is one of the iefforts to prepare the millennial generation to face marriage and produce healthy and quality offspring. The characteristics of millennial generation who understand information technology and the occurrence of a pandemic are the reasons to use online communication media in nutrition education. This study aims to determine the most effective combination of online communication media (Microsoft Sway-Whatsapp and Microsoft Sway-Zoom Cloud Meeting) used in preconception nutrition education for the millennial generation. The study used a quasi-experimental method with a nonequivalent control group pre-test and post-test design. Samples of 60 people obtained by the purposive sampling technique. Quantitative data on nutritional knowledge between groups were analyzed by independent t-test. Research shows that using a combination of online communication media can effectively improve educational outcomes. There is no significant difference in the results of millennial nutrition education in the use of the two combinations of online communication media, but the use of the Microsoft Sway-Whatsapp combination is considered to give better results because it is considered practical, easy to use, and does not require more quota pulses. The use of online communication media in education is necessary. considering media capabilities, internet network, and access costs for optimally goals.